Comparative evaluation of chemiluminescent immunoassay and enzyme‐linked immunosorbent assays for the diagnosis of West Nile virus infections. Issue 4 (1st March 2022) - Gómez‐Vicente, Esther; Garcia, Rafael; Calatrava, Elizabeth; Olivares Duran, María Jose; Gutiérrez‐Bautista, Juan Francisco; Rodriguez‐Granger, Javier; Cobo, Fernando; Navarro Mari, Jose Maria; Sampedro‐Martinez, Antonio
Abstract : In August 2020, anew West Nile virus (WNV) outbreak affected 71 people with meningoencephalitis in Andalusia (Spain). Samples from these individuals were received in our laboratory, a regional Virus Referral Centre. The aim of this study was to compare the agreement, sensitivity and specificity of findings between the WNV VIRCLIA IgG and IgM assay (Vircell, Spain) and the WNV ELISA IgM and IgG assay (Euroimmun, Germany) and to compare the performance of WNV VIRCLIA IgM and Euroimmun ELISA for cerebrospinal fluid (CSF) diagnosis. The study included 24 CSF samples (paired with serum samples) and 247 serum samples from 217 patients with suspected WNV infection (1 or 2 per patient). The agreement between ELISA and CLIA tests for IgM and Ig G detection in serum was 93% (kappa index = 0.85) and 96% (kappa index = 0.89) respectively. Sensitivity values of ELISA and CLIA tests for IgM in serum samples were 96.7% and 98.9%, respectively, and specificity values were 96.4% and 95.4% respectively. Sensitivity values of ELISA and CLIA test for IgG in serum samples were 91.1% and 97%, respectively, and specificity values were 100% and 98.8% respectively. Results obtained with ELISA and CLIA tests in CSF samples showed 75% agreement between them (kappa index = 0.51). According to these findings, the WNV VIRCLIA IgM and IgG monotest offers an accurate qualitative detection of WNV in serum and CSF specimens.